Perceived Benefits and Intakes of Protein, Vitamin C and Iron in Preventing Anemia among Pregnant Women - Mira Triharini; Nursalam Nursalam; Agus Sulistyono; Merryana Adriani; Pei-Lun Hsieh (Jurnal Ners, 2018)
Introduction: Nutritional adequacy is essential in ensuring the normal growth and development of the fetus. Perceived benefits will be able to strengthen pregnant women to meet optimum nutritional intake to prevent anemia. Adequacy of protein, vitamin C and iron will reduce the risk of iron deficiency anemia in pregnancy. This study aims to examine the association between perceived benefits with protein, vitamin C, and iron intake in preventing pregnancy anemia.Methods: This study used a cross-sectional design and was conducted in August-October 2017 among105 pregnant women. This study used the multistage random sampling method. The population of this study was pregnant women who had antenatal care in four Community Health Centre in Surabaya namely Jagir, MedokanAyu, SidotopoWetan, and Gundih. Results: The average daily protein intake was 76.34 (SD = 35.88) gram/day. There was a significant association between perceived benefits with protein intake (r = 0.272; p = 0.005). The average daily vitamin C intake was 90.67 (SD = 116.54) mg/day. There was no significant association between perceived benefits and vitamin C intake (r = 0.175; p = 0.074). The average daily iron intake was 64.73 (SD = 23.13) mg/day. There was a significant association between perceived benefits and iron intake (r = 0.219; p = 0.025).Conclusion: The knowledge of pregnant women about the benefits of nutrition will affect the adequacy of pregnancy nutrition. Health workers need to provide health education on the importance of nutrition for pregnant women to prevent anemia during pregnancy.